2009
DOI: 10.1080/00015458.2009.11680439
|View full text |Cite
|
Sign up to set email alerts
|

A Quality of Life Comparison of Laparoscopic and Open Approaches in Acute Appendicitis: A Randomised Prospective Study

Abstract: Laparoscopic appendectomy is a safe method, which also has advantages of diagnostic procedure for other pathologies, a better quality of life both in the early and late period, and a short hospital stay. The important advantage is also seen in the late period with better quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…It is also gaining popularity because of shorter operative time, less postoperative pain, and lesser incidence of surgical site infection [8][9][10][11][12][13][14]. Its only drawback is slightly higher rate of intra-abdominal abscess [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…It is also gaining popularity because of shorter operative time, less postoperative pain, and lesser incidence of surgical site infection [8][9][10][11][12][13][14]. Its only drawback is slightly higher rate of intra-abdominal abscess [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…However, several randomized controlled trials comparing laparoscopic with open appendectomy have provided conflicting results [9,10]. Previous studies have demonstrated better clinical short-term outcomes with the laparoscopic approach [11][12][13], while other studies have shown marginal or no short-term clinical benefits [14][15][16]. Bearing in mind that laparoscopic appendectomy, unlike other laparoscopic procedures, has not been found superior to open surgery for acute appendicitis [17].…”
Section: Introductionmentioning
confidence: 96%
“…After eliminating duplicate articles, we evaluated the titles and abstracts of these studies according to the inclusion and exclusion criteria, after which 61 articles remained. After the full texts of these articles were read and the ineligible studies were excluded, 29 randomized controlled trials involving 2134 laparoscopic appendectomy (LA), in addition to 2177 open appendectomy (OA) [10][11][12][13][14][15]. The characteristics of these studies are listed in the Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, it also conflicts with previous studies comparing LA and OA in terms of quality of life in both the short-term and the long-term in which better quality of life has been associated with LA. [18][19][20] Preference for the laparoscopic approach over the open approach in uncomplicated appendicitis is still justified because of the important role of laparoscopic appendectomy in surgical training and patient preference for minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 99%